The effect of information technology on coastal development in Asahan Regency, North Sumatra Province, Indonesia. Issue 1 (November 2021) - Syafiq, M; Sirojuzilam,; Badaruddin,; Purwoko, A
Abstract: This research aims to examine the relationship between information technology and coastal development in Asahan Regency, North Sumatera Province, Indonesia. Through this research, coastal community opinions were collected using structured questionnaires. A structural equation modeling (SEM) approach was employed to test a hypothesized model constructed based on theories and previous studies. In addition, a new combination of existing indicators was used as a novelty of this research. The research result indicates that information technology has not significantly affected coastal development. Theoretical and practical implications of the research findings for policymakers are discussed.